Improving The Quality Of Education In Indonesia With The "Kartini" Approach - Gusni Cahaya Putri; Evandito Raihan Prayoga; Prio Agus Santoso (Proceeding of the International Conference on Global Education and Learning, 2024)
The decline in the quality of education in Indonesia is caused by unplanned curriculum changes, a shortage of competent educators, and a lack of good manners and behavior among students and educators, which hinders the achievement of educational goals to create a smart, qualified, and competitive generation at the global level. The purpose of writing this essay is to explore and develop thoughts on how the "KARTINI" Approach is to improve the quality of education in Indonesia by emphasizing six key values: Culture, Artificial Intelligence (AI), Taqwa, Integrity, Nationalism, and Independence. Culture-based education aims to cultivate students' character rooted in the nation's cultural values and the ability to adapt to changing times. The application of AI in education allows for more personalized and effective learning, while the value of piety teaches morality and spiritual awareness. Integrity forms an honest and responsible character, nationalism builds a sense of love for the homeland, and independence teaches independence. By integrating these values, Indonesian education is expected to produce a generation that excels academically and has a strong character to contribute to the progress of the nation.